Lectotypification and taxonomic identity of Orthostichopsis subtenuis (Pterobryaceae) - Vilas Bôas-Bastos, Silvana B.; Bastos, Cid José Passos (Phytotaxa, 2016)
A taxonomic study of Pterobryaceae in Brazil indicates the need to lectotypify Orthostichopsis subtenuis, and to consider this taxon under synonymy with Orthostichella pachygastrella (Neckeraceae). Both names are clearly conspecific on the basis of various morphological characters.